Application of analytic network process and GIS for evaluating integrated coastal land use in Kuala Langat district, Selangor, Malaysia - Abadi, Sharareh Pourebrahim (2008)
Coastal lands are increasingly threatened by short-sighted planning policies that have focused on human activities rather than the systems sustaining them. Evaluation of coastal land uses for sustainable development involves the identification of the most important criteria and indicators. Analytic Network Process (ANP) is a new method that has potential application in the field of coastal land use development. The purpose of this research was to develop an integrated approach for evaluating the suitability of different kinds of land uses in the coastal area for sustainable development. The coastal area of Kuala Langat District, Selangor, Malaysia, was selected as the study area. There were two main objectives in this research. The first was to identify the most important criteria for coastal land use development and the second was to find the optimal land utilization suitability based on different planning scenarios. Two different approaches were applied to achieve these objectives. For the first objective, the approach employed was multi criteria evaluation using Analytic Network Process by expert opinion. For the second objective, the spatial scenario evaluation using ARCGIS software was adopted. Three scenarios residing on economic and social development, environmental conservation and sustainable development were defined and evaluated. Four land uses, namely, residential, conservation, tourism and industry were considered. Through evaluation of the scenarios, existing plans and guidelines, land availability and investigation of current land uses and the optimum suitability for sustainable coastal land use development were proposed. The research has demonstrated an innovative reliable method for identification of the best criteria using ANP and expert opinion. This is the first time ANP has been used for criteria development in coastal land use planning. A new software with the capability of choosing the best criteria for ANP was also developed. The current and future project patterns of growth till the year 2020 were analyzed. The GIS database for the study area was developed for scenario analysis. This analysis has resulted in a series of suitability maps for conservation, tourism, residential and industrial development. However, considering the sustainable development scenario, only one optimal land suitability map was recommended, based on criteria obtained from ANP and expert knowledge. The spatial scenario planning framework developed in this research is an example of an effective integrated decision-making framework. This research has successfully managed to identify and develop a scientifically based method to find the optimal land suitability for sustainable development in coastal land uses. The integration of social, economic and environmental criteria within the planning framework has provided an efficient spatial approach for coastal land use development. It is hoped that this ANP based approach can be employed in land use suitability assessments at both the local plan and structure plan level.